Gut microbiota changes associated with Clostridioides difficile infection and its various treatment strategies - Anne J. Gonzales-Luna; Travis J. Carlson; Kevin W. Garey (Gut Microbes, 2023)
ABSTRACTHuman gut microbiota are critical to both the development of and recovery from Clostridioides difficile infection (CDI). Antibiotics are the mainstay of CDI treatment, yet inherently cause further imbalances in the gut microbiota, termed dysbiosis, complicating recovery. A variety of microbiota-based therapeutic approaches are in use or in development to limit disease- and treatment-associated dysbiosis and improve rates of sustained cure. These include the recently FDA-approved fecal microbiota, live-jslm (formerly RBX2660) and fecal microbiota spores, live-brpk (formerly SER−109), which represent a new class of live biotherapeutic products (LBPs), traditional fecal microbiota transplantation (FMT), and ultra-narrow-spectrum antibiotics. Here, we aim to review the microbiome changes associated with CDI as well as a variety of microbiota-based treatment approaches.